ICT-Based Gamification Application: Supporting the Implementation of Team Games Tournament Cooperative Learning Model to Improve Students’ Learning Outcomes - Umacina, Fitri Liliyani; Hamid, Fatma; Saprudin, Saprudin; Rahman, Nurdin Abdul; Saputra, Aji (TECHNO: JURNAL PENELITIAN, 2024)
This research aims to improve students’ learning outcomes through the implementation of the Team Games Tournament (TGT) cooperative learning model complemented with ICT-based gamification applications. This research is an experimental research that involved students from class VIII at a junior high school in Ternate city. Students’ learning outcome data were collected through multiple-choice test instruments. The results showed that the use of the Wordwall gamification application in the TGT cooperative learning model was significantly more effective to improve students’ learning outcomes compared to conventional learning. This research implies that ICT-based gamification applications can be used as a complement to teaching materials. Moreover, the variety of game types utilized contributes to increased student engagement in the learning process.